Smart Grid Stability Enhancement using Waterwheel Plant Algorithm for Demand Side Management - Askar, Sami; Uma, S.; Sethi, Gaurav; Ramkumar, M. Siva; Dhivya, S.; N, Rajesha (2025 7th International Conference on Inventive Material Science and Applications (ICIMA), 2025)
Demand-Side Management (DSM) within Internet of Things (IoT)-enabled Smart Grids (SGs) employs advanced communication automation and intelligent control techniques to manage electricity consumption. One of the disadvantages of DSM in IoT-enabled SGs is that demand forecasting is inaccurate due to uncertainties in consumption patterns of electricity and Renewable Energy (RE) generation, leading to inefficient load scheduling and increasing errors in energy distribution. To address these issues, this paper proposes a Waterwheel Plant Algorithm (WPA) is utilized to optimize DSM in SGs by enhancing energy efficiency, improving load balancing, and reducing forecasting errors for better grid stability. The WPA is used to minimize Mean Squared Percentage Error (MSPE) for securing DSM in SGs. Its adaptive optimization ensures that minimize forecasting errors across operating conditions thereby enhancing overall efficiency of the energy distribution system. By then proposed WPA method is implemented on the MATLAB platform, and its performance is evaluated by comparing it with existing optimization techniques such as Binary Orientation Search Algorithm (BOSA), Ant Colony Optimization (ACO), Binary Particle Swarm Optimization and Gravitational Search Algorithm (BPSOGSA), Modified Elephant Herd optimization algorithm (MEHOA), and Arithmetic Harris Hawks Optimization (AHHO). The results show that the proposed WPA method provides superior performance in minimizing MSPE, achieving the lowest MSPE value of 2.05%, indicating its enhanced accuracy DSM in SGs.